Reactive astrocyte-derived neurotoxicity is mitigated by vitronectin in traumatic brain injury mouse model - Minori Yamashita; Nito Nakahira; Kei Hashimoto; Hirono Kobayashi; Mari Nakashima; Hiroko Ikeshima-Kataoka; Yasunori Miyamoto (IBRO Neuroscience Reports, 2025)
Vitronectin (VN) is an extracellular matrix protein that contributes to brain injury repair by regulating the fibrinolytic system. VN interacts with glial cells to regulate cytokine production. However, it is unclear how VN affects glial dynamics to promote repair of brain injury in a mouse model of traumatic brain injury (TBI). Here, we examined the effect of VN on astrocyte dynamics and neuronal cell death in mouse cerebral cortices after stab wounds. First, we verified that Vn-/- cortices with stab wound surgery showed severe neuronal cell death and astrocyte activation around the lesion. In addition, the concentration of complement C3 was increased in Vn-/- cortices after the stab wound, which was co-localized with astrocytes, suggesting that VN regulates astrocyte-derived C3 secretion and attenuates neurodegeneration after TBI. To further examine this, we collected secretions from VN-treated primary astrocytes and added them to primary cortical neurons, and found that secretions from VN-treated astrocytes have low neurotoxicity. Because the secretion from VN-treated astrocytes contained high levels of C3, we treated primary cortical neurons with the secretion from astrocytes and an inhibitor of the complement pathway, CD59, and analyzed neuronal cell death; results showed that inhibition of the complement pathway attenuates astrocyte secretion-induced neuronal apoptosis. Our results indicate that VN exerts a neuroprotective function through the suppression of C3 secretion from astrocytes. Therefore, VN plays a role in mitigating neurodegeneration after TBI by suppressing complement C3 secretion from reactive astrocytes.